Analysis of Chloride Contaminant Transport in Tailings Storage Facility Dam (Case Study: Gold Mine in Sumatra) - Devina Pascayulinda; Budijanto Widjaja; Martin Wijaya (Journal of the Civil Engineering Forum, 2024)
In the practice of gold mining industry, hazardous waste known as tailings is produced during the ore extraction process. These tailings are typically stored in a dam structure called a Tailings Storage Facility (TSF). The planning and construction of a TSF are critical considerations, as the failure of a TSF can have substantial environmental impacts, pose risks to human safety, and result in industrial losses. Therefore, strict control is necessary in the development of TSFs to minimize the potential negative consequences. This research focuses on the transport of contaminants within a TSF, specifically examining the concentration of chloride contaminants and conducting particle movement analysis. The study utilizes modeling through the GeoStudio SEEP/W program to simulate groundwater flow profiles and the GeoStudio CTRAN/W program to understand contaminant movement over a 100-year period. GeoStudio modeling employs 10 materials: impermeable clay soil, filter sandy soil, transition gravel rock, three mine waste types (Fine, Rockfill, and Rockfill with fine), hard rock bedrock layer, in-situ soil representing the original layer, landslide with colluvial soil, and the tailings itself. Back analysis is employed to iterate model parameters and ensure modeling accuracy against field data, including comparisons with water quality test results and readings from vibrating wire piezometer (VWP) instrumentation. The contaminant transport is influenced by advection-dispersion processes and tends to concentrate within the TSF boundary toward the dam toe over a 100-year timeframe. The analysis emphasizes the influence of advection in contaminant transport and underscores the importance of particle position relative to the groundwater level, with Particle Tracking Analysis shows significant movement within the groundwater flow area. This research provides crucial insights into the dynamics of contaminant concentration, informing better decision-making in TSF planning and management. The findings underscore the imperative of strict control measures to minimize environmental impacts and human safety risks associated with TSFs, thereby advancing knowledge in gold mining waste management.